Engineering the User Interface From Research to Practice - Redondo, Miguel; Bravo, Crescencio; Ortega, Manuel (Springer London : Imprint: Springer, 2009)
This book contains a selection of sixteen high-quality papers presented at the 7th International Conference on Interacción Persona-Ordenador (IPO), which stands for Human-Computer Interaction in Spanish and was called Interacción'2006 for short). This conference took place in Puertollano (Ciudad Real, Spain) on November 13th-17th, 2006, and was organized by the CHICO research group from the Universidad de Castilla - La Mancha (Spain). In its seventh edition this conference has become a multidisciplinary forum for the discussion and dissemination of novel research in Human-Computer Interaction (HCI). The main goals of Interacción'2006 were threefold: to spread innovative research and promote discussion on HCI; to put in contact research groups from all over the world, mainly Spanish-speaking groups and the most authoritative researchers in the field; and to enrich the relationship between academia and industry in all the topics related to HCI. This volume is organized according to the main areas of both basic and applied research that were presented at the conference: Ergonomics and Human Factors, Usability and Accessibility, Ambient Intelligence and Context-aware Systems, User-Centred Design, Systems and Models for Collaborative Work, HCI in e-Learning, User Interface Design and Development, Virtual and Augmented Reality, Multi-modal Interaction, Ubiquitous Computing Devices and Applications, HCI for People with Special Needs. The primary audience of this book includes, but it is not limited to, researchers and practitioners in HCI, developers and users of HCI systems, and institutions involved in the development and standardization of HCI technologies.